2005
DOI: 10.1007/s10549-005-9024-8
|View full text |Cite
|
Sign up to set email alerts
|

Provasopressin expression by breast cancer cells: implications for growth and novel treatment strategies

Abstract: SummaryThe arginine vasopressin (AVP) gene is expressed in certain cancers such as breast cancer, where it is believed to act as an autocrine growth factor. However, little is known about the regulation of the AVP protein precursor (proAVP) or AVP-mediated signaling in breast cancer and this study was undertaken to address some of the basic issues. The cultured cell lines examined (Mcf7, Skbr3, BT474, ZR75, Mcf10a) and human breast cancer tissue extract were found to express proAVP mRNA. Western analysis revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 54 publications
5
48
0
Order By: Relevance
“…Furthermore, in vitro studies have suggested a potential clinical application for V1a antagonists in treating cancer or renal disease (266,399,479).…”
Section: B V1a and V1b Receptor Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in vitro studies have suggested a potential clinical application for V1a antagonists in treating cancer or renal disease (266,399,479).…”
Section: B V1a and V1b Receptor Antagonistsmentioning
confidence: 99%
“…In vitro studies have shown that the proliferative effects of AVP on cells derived from tumors are inhibited by SR49059 (relcovaptan) (266,399). Since the V1a receptor is widely expressed in various malignant cells, including neuroendocrine tumors (378) and small cell lung cancer (319), the AVP/V1a axis may represent a novel target for antitumor therapies.…”
Section: Tumorsmentioning
confidence: 99%
“…The majority of work carried out to date on this neuropeptide hormone has concentrated on its multiple neurophysiological functions (Rogge et al ., 2008). A role for neuropeptides in breast cancer is not without precedence, for example, neuropeptide Y, nerve growth factor, Oxytocin and Vasopressin have all long been associated with disease progression (Taylor et al ., 1990; Dolle et al ., 2004; Keegan et al ., 2006; Ruscica et al ., 2007; Adriaenssens et al ., 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the effects observed are believed to result from a direct action of the antibody on the tumor cells because MAG-1 was found by us to react only with anterior hypothalamus and neurohypophysis, and not with other mouse tissues, nor with 66 normal human tissues [20]. While vasopressin and its receptors play a role in tumor breast cancer growth [7, 8, 12], the exact role of provasopressin as a surface protein remains a mystery and might not be directly connected to the mitogenic action of the hormone. Provasopressin is not a ligand for vasopressin receptors, and could itself, for these tumors, represent a receptor or scaffolding molecule for an as yet unknown ligand.…”
Section: Discussionmentioning
confidence: 99%
“…A similar tumor marker on small-cell lung cancer can be targeted in patients with antibodies [10]. A mouse IgG1 monoclonal antibody, MAG-1, directed against a C-terminal segment of provasopressin has been shown by us to give positive immunohistochemical staining with all breast cancer tissues examined, and to highlight the presence of this protein on the surface of breast cancer cells in culture [11, 12]. In this study, we examined the ability of MAG-1 and 90 Yttrium-labeled MAG-1 to arrest the growth of breast cancer xenografts in nu/nu mice.…”
Section: Introductionmentioning
confidence: 99%